2021
DOI: 10.3390/plants10071434
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogenetic Diversity and Biological Characterization of Diaporthe Species Associated with Leaf Spots of Camellia sinensis in Taiwan

Abstract: Camellia sinensis is one of the major crops grown in Taiwan and has been widely cultivated around the island. Tea leaves are prone to various fungal infections, and leaf spot is considered one of the major diseases in Taiwan tea fields. As part of a survey on fungal species causing leaf spots on tea leaves in Taiwan, 19 fungal strains morphologically similar to the genus Diaporthe were collected. ITS (internal transcribed spacer), tef1-α (translation elongation factor 1-α), tub2 (beta-tubulin), and cal (calmod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 61 publications
(116 reference statements)
0
3
0
Order By: Relevance
“…We found that starch is the most suitable carbon source for its growth, while peptone is the preferred nitrogen source. The observations in this study are consistent with those of Fu et al [45], Yan et al [46], and Ariyawansa et al [47].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We found that starch is the most suitable carbon source for its growth, while peptone is the preferred nitrogen source. The observations in this study are consistent with those of Fu et al [45], Yan et al [46], and Ariyawansa et al [47].…”
Section: Discussionsupporting
confidence: 94%
“…Fu et al [45] found that the optimal temperature range for Phomopsis mangiferae Ahmad growth was 25-30 • C. Yan et al [46] found that the optimum carbon source for Diaporthe eres growth was starch and the optimum nitrogen source was peptone. In a recent study, Ariyawansa et al [47] identified six Diaporthe species associated with leaf spot disease of C. sinensis in Taiwan tea fields, and found that the optimal temperature for mycelium growth was 25-30 • C, with a preference for growth in a low-acid-alkaline medium. In this study, through experiments employing different carbon and nitrogen sources, acid and alkaline conditions, and temperatures, the preference and growth requirements of the D. passiflorae strain to specific environments were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…They are compliant and occur as pathogens, endophytes, and saprobes in a wide range of hosts [ 4 ]. As plant pathogens, Diaporthe species can cause leaf spots, blights, dieback, scab, decay, stem-end rots, trunk, or even wilt diseases including many economically important plants such as Blueberry [ 5 ], Camellia [ 6 ], Citrus [ 7 ], Coffea [ 8 ], Helianthus [ 9 ], Lithocarpus [ 8 ], Pyrus [ 10 ], Senna [ 11 ], and Vitis [ 12 ]. In addition, Diaporthe species are often reported as endophytes [ 13 , 14 ] that live inside the healthy host tissues, without showing any physical symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…However, D. hongkongensis could be easily distinguished by the production of gamma conidia [24], which were not observed in D. africana. Diaporthe hongkongensis has been reported only from Asia, including China, Japan, Taiwan, and Turkey [24,[59][60][61][62].…”
Section: Molecular Phylogeny and Taxonomymentioning
confidence: 99%